Ludic Strategy and Ludological Studies in Glottodidactics – Inspirations, Research and Perspectives - Surdyk, Augustyn (Hamburg: Verlag Dr. Kocač, 2020)
Ludology, known also as games research and game studies, has gained throughout decades an increasing popularity all around the world among scholars dealing with various ludic activities and researching them from numerous perspectives. Ludologists originate from innumerable disciplines encompassing sciences, social sciences and humanities, among others including linguistics, applied linguistics and glottodidactics. In every country there are to be found outstanding researchers in this field inspiring by their impressive achievements next generations of followers. One of them, in Poland, is Prof. Teresa Siek-Piskozub from Adam Mickiewicz University in Poznań. The aim of this article is to present selected examples of the influence of her work on both individual and global academic, educational, organisational and institutional enterprises initiated by scholars conducting research in the field of games and broadly perceived ludic phenomena, as well as educators and practitioners.
Keywords: ludology; games research; game studies; ludic strategy; ludic techniques; glottodidactics; Games Research Association of Poland; Technique of Role-Playing Games